Traditional Initiation Rites: Constraints on Students' Educational Attainment in Coast Region Tanzania - Benson, Audrey; Nemes, Joyce; Nguru, Festo (CV. Literasi Indonesia, 2025)
Traditional initiation rites remain integral to cultural identity and coming-of-age practices in many African societies, significantly influencing educational outcomes. While existing literature predominantly emphasizes the negative impacts of these practices on education, limited research explores their comprehensive effects on female students' educational attainment, particularly in the coastal region of Tanzania. This study aimed to investigate how traditional initiation rites influence students' educational attainment in the Chalinze District, Coast Region, in the United Republic of Tanzania. Guided by Vygotsky's Sociocultural Theory, the study employed a qualitative approach, collecting data through interviews, focus group discussions, and documentary reviews involving educational officers, teachers, parents, and students. The findings revealed a complex interplay between traditional practices and education, where initiation rites caused significant academic disruptions and behavioral transformations. Notably, key findings indicated that, in addition to post-initiation autonomy, ceremonial gift-giving practices and teachings from traditional instructors frequently resulted in educational challenges, including dropouts, early marriages, and teenage pregnancies. The study concludes that, while traditional rites hold cultural significance, their current implementation patterns considerably constrain educational attainment. This research contributes to understanding the cultural-educational nexus in Tanzania and recommends reforming initiation practices to align with educational goals, implementing cultural education programs, and establishing collaborative frameworks between traditional authorities and educational institutions to harmonize cultural practices with academic achievement.